68Ga-PSMA-HBED-CC PET/CT imaging in Black versus White South African patients with prostate carcinoma presenting with a low volume, androgen-dependent biochemical recurrence: a prospective study. Issue 2 (February 2018) - Lengana, Thabo; van de Wiele, Christophe; Lawal, Ismaheel; Maes, Alex; Ebenhan, Thomas; Boshomane, Tebatso; Zeevaart, Jan R.; Ankrah, Alfred; Mokgoro, Neo; Vorster, Mariza; Sathekge, Mike
Abstract : Objective: To compare the diagnostic accuracy of 68 Ga-prostate-specific membrane antigen (PSMA)-HBED-CC PET/computed tomography (CT) imaging for the detection of androgen-dependent recurrent prostate carcinoma (ADPC) in Black South Africans (BSAs) versus White South Africans (WSAs) with increasing serum prostate-specific antigen (PSA) values below or equal to 10 ng/ml. Patients and methods: A total of 61 patients with ADPC were prospectively included in the study (mean age: 66.7 years): 38 WSAs and 23 BSAs. 68 Ga-PSMA-HBED-CC PET/CT imaging results obtained were related to serum PSA levels and to ethnicity. Results: A total of 41 (67%) patients had a positive 68 Ga-PSMA-HBED-CC scan result. 68 Ga-PSMA-HBED-CC PET/CT positivity was significantly higher in patients with PSA values more than 2 ng/ml [32/38 (84%) patients] when compared with patients with PSA values less than 0.5 ng/ml [6/11 (55%) patients] or PSA values of 0.5–2 ng/ml [3/12 (25%) patients] ( P =0.0001). Mean PSA values proved not significantly different in patients presenting with extrapelvic involvement when compared with those with intrapelvic involvement or between patients who presented with bone involvement versus those who did not on 68 Ga-PSMA-HBED-CC PET/CT) ( P ≥0.147). Age, Gleason-scores, median PSA values, the frequency of a positive scan result, the frequency of bone involvement, and extrapelvic involvement proved similar in WSAs and BSAs ( P ≥0.417). Conclusion: 68 Ga-PSMA-HBED-CC PET/CT imaging identified a recurrence in 67% of the patients under study. Higher PSA levels were associated with 68 Ga-PSMA-HBED-CC PET/CT positivity and the detection rate. Imaging results obtained proved similar in BSAs and WSAs, suggesting that the tumor burden and growth rate of ADPC are similar in both races.